Pembuatan Jig And Fixture Untuk Mempermudah Proses Perakitan Part Pada Bagian Auto Section (Ai) - P. Yudi Dwi Arliyanto; Fritz Gamaliel; Diah Ayu Fitriani (Prosiding Sains dan Teknologi, 2022)
In a production process, optimal processing time is required. Jigs and fixtures are indispensable tools in the process of making components or workpieces to ensure their versatility and suitability. In addition, also to help simplify and speed up the work process. The problem that has occurred so far is the amount of time it takes just to install the body mic body so that the production results are less than optimal. In the electronics industry, especially in the assembly of parts on the body mic, it is always done manually so that the process takes longer. This becomes less effective in the production process. The purpose of making this study is to provide improvements that help simplify and speed up the body mic assembly process. Therefore, the jigs and fixtures were designed using the method of analysis with the remaining material, then assembling them with the specified design to facilitate the installation process. The designed tool is a tool for assembling the body part of the body mic. The results of this study show that using jigs and fixtures makes the process of assembling the body mic part faster and more efficient. Keywords: Body Mic, Jig, Fixture, Assembling